Lisbon heat island statistical study (2004-2012) - Alcoforado, Maria João; Lopes, António; Alves, Elis Dener Lima; Canário, Paulo (Finisterra, 2014)
With the aim of implementing climatic guidelines for planning purposes,the urban climate of each particular city must be assessed, particularly the frequency ofunwanted climatic features, such as the Urban Heat Island (UHI). As the Lisbon “Mesoscaleurban meteorological network” (CEG-IGOT-ULisboa) has been running since 2004, it isnow possible to present statistical results about the UHI. It was calculated on an hourly basisas the difference between one of the “central” measurement points (Restauradores orSaldanha) and one of the eccentric points of the network (Carnide or Monsanto). UHI ismore intense in summer (maximum hourly averages up to 6.3ºC) than in winter (up to 3.8ºC),and more intense during the night than during the day. In Lisbon, its causes are not only dueto the modification of energy balance in urban areas, but also to the shelter effect from theprevailing and cold/cool North winds, due to the topography and the buildings.